AI, Ai, and I: Mapping Marxist and Afrofuturist Approaches to Plagiarism and ChatGPT Through Pauline Hopkins - Len von Morzé (Radical Teacher, 2025)
This essay argues that teaching ChatGPT and other generative AI technologies in writing-intensive courses should not merely attempt to offer students guidance on responsible use of this transformative technology. Instead, the essay outlines a Marxist approach for teaching AI as a phase in the expropriation of labor. It then turns to pedagogical strategies for contextualizing a novel by Pauline Hopkins, as well as the recent controversy around it, that can put AI into historical perspective. The Afrofuturist novel, the essay shows, can demonstrate ways that labor expropriation, as well as the definition of plagiarism as theft of propertym have been racialized.